Changing patterns of allotment gardening in the Czech Republic and Slovakia - Tóth, Attila; Duží, Barbora; Vávra, Jan; Supuka, Ján; Bihuňová, Mária; Halajová, Denisa; Martinát, Stanislav; Nováková, Eva (Berghahn Journals, 2018)
Allotment gardens have played a significant role in Czech and Slovak society for decades, building upon a rich history of gardening. This article elaborates on Czech and Slovak allotments in the European context and identifies their core functions, services, and benefits. We provide a thorough historical review of allotments in this region, reaching back to the eighteenth century to trace significant periods and historic events that shaped society in general and urban gardening in particular. We analyze the development of allotments until and after 1989 and illustrate key aspects of their present situation using case studies and examples. The article provides a complex historical narrative as a good basis for discussions on contemporary trends, challenges, and visions for the future of urban allotment gardening in both countries.
Keywords: allotments; civil society; Eastern Europe; political change; spatial planning and development; urban agriculture